Anthropometric and physical fitness characteristics of female basketball players in South Africa - Mtsweni, L. B.; West, S. J.; Taliep, M. S. (South African Journal for Research in Sport, Physical Education and Recreation, 2017)
The anthropometric and physical fitness characteristics of South African (SA) female university-level, provincial-level and national-level players were examined in order to provide possible reasons for their poor performance. Fifty-five participants were recruited for the study. These included 24 university-level, 17 provincial-level, and 14 national team players. Anthropometric data included age, stature, body mass, sum of seven skinfolds and percentage body fat. The fitness characteristics included flexibility, strength, explosive power, muscular endurance, agility, speed and aerobic endurance. The national team players were significantly taller than both the provincial-level and university-level players. Fitness test results indicated that the national team players were significantly better than the universitylevel players in only three of the tests (hamstring flexibility, upper body muscle power and agility). Provincial-level players performed significantly better than the national team players in the aerobic fitness test. The anthropometric and physical fitness characteristics of female basketball players in SA are poor and could be a major contributing factor to their low international ranking.